The Acceptance of Industrialised Building Systems - Ng, Choon Eu (2014)
This study is to evaluate the level of acceptance for Industrialised Building Systems (IBS) implementation in Malaysia Industrialised Building System know as prefabrication a construction which components are manufactured in a factory or site factory according to a standardize shapes and dimension that could be transported to construction site from a building. In this research, I would need to determine the obstruction factors and problems in using IBS and also the perception from construction industry. After that I would evaluate the IBS level of acceptance in Malaysia. Based on result from Construction Industry Development Board (CIDB)-IBS Roadmap 2011 -2015, their data collected from two sectors: Private Sector and Government sector, As per their result, the usage of IBS content in private sector is less than 35% while Government sector contains of 70% usage. My research respondents are also from the construction industry 53% of them is from private sector and 47% of them are from Government sector. 75% of my respondents are participating in IBS and 80% of the respondent are accepting IBS and would recommend IBS to others in future. I also managed to find out the reason of why IBS is not effective and the benefit of IBS in Malaysia in this research paper. From my research, I would say that IBS is starting to be picking up in the Malaysia, it would be more effective if government cold provide more workshop on IBS